Temporal specificity of training: intra-day effects on biochemical responses and Olympic-Weightlifting performances - Ammar, A.; Trabelsi, C. K.; Padulo, J.; Turki, M.; El Abed, K.; Hoekelmann, A.; Hakim, A. (Journal of Sports Sciences, 2015)
The aim of this study was to investigate the performance of an Olympic-Weightlifting session training at three times of the day on the performance related to biochemical responses. Nine weightlifters (21 ± 0.5 years) performed, in randomised order, on three Olympic-Weightlifting training (snatch, clean and jerk) sessions (08:00 a.m., 02:00 p. m., 06:00 p. m.). Blood samples were collected: before, 3 min and 48 h after each training session. Haematological parameters and markers of muscle injury were assessed. Resting oral temperature and rating of perceived exertion (RPE) were also assessed during each session. ANOVA showed that the performance was better (P < 0.001) at 02:00 p. m. with a less RPE (P < 0.01) compared to the morning and the evening sessions while there was higher (P < 0.05) oral temperature at 06:00 p. m. versus 08:00 a.m. and 02:00 p. m. Muscle damage changed immediately (without significant effect after 48 h) after the training sessions with lower values in the evening compared to the morning. In conclusion, the afternoon training is more effective than morning or evening sessions for weightlifters. Therefore, coaches and weightlifters should be advised to schedule their training session in the afternoon hour.